ANALISIS PROFESIONALISME GURU PAUD DALAM IMPLEMENTASI KURIKULUM MERDEKA : TANTANGAN DAN SOLUSI PADA ASPEK PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) - Ilun Muallifah; Bella Puspita; Fifi Aulia zuliana; ‘Ushoifiroh (STKIP Subang, 2026)
This qualitative study explores teacher professionalism in implementing the Pancasila Student Profile Strengthening Project (P5) within early childhood education, focusing on planning, execution, and resource management. The findings emphasize that P5 serves as a vital tool for character formation, prioritizing the quality of the exploration process over physical outputs through child-centered Project-Based Learning supported by digital media. To overcome technical obstacles and misaligned perceptions, the study highlights the importance of regular teacher discussions and intensive communication with parents via consultative bodies. Ultimately, the successful synergy between professional educators and supportive parents led to significant improvements in children's independence, social collaboration, and daily etiquette, proving that collaborative leadership is essential for the sustainable development of student character at an early age.